2007
DOI: 10.1021/jf062816a
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of (−)-Epigallocatechin-3-gallate in Conscious and Freely Moving Rats and Its Brain Regional Distribution

Abstract: A liquid chromatography technique coupled with tandem mass spectrometry (LC-MS/MS) electrospray ionization was used to measure (-)-epigallocatechin-3-gallate (EGCG) in rat plasma. This method was applied to investigate the pharmacokinetics of EGCG in a conscious and freely moving rat by an automated blood sampling device. Multiple reaction monitoring (MRM) was used to monitor the transition of the deprotonated molecule m/z of 457 [M - H]- to the product ion 169 for EGCG and the m/z of 187 to 164 for the intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
119
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(125 citation statements)
references
References 23 publications
6
119
0
Order By: Relevance
“…13,14) In the oral administration group, EGCG, EGCG3″Me, and EGCG4″Me were dissolved in 1 mM HCl/1 mM ascorbic acid/10% polyethylene glycol prior to oral administration at a dose of 100 mg/kg. Blood samples were withdrawn through the cannula at 0.25, 0.5, 0.75, 1, 1.5, 2, 3, 4, 6, 8, and 24 h after administration.…”
Section: Chemicalmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14) In the oral administration group, EGCG, EGCG3″Me, and EGCG4″Me were dissolved in 1 mM HCl/1 mM ascorbic acid/10% polyethylene glycol prior to oral administration at a dose of 100 mg/kg. Blood samples were withdrawn through the cannula at 0.25, 0.5, 0.75, 1, 1.5, 2, 3, 4, 6, 8, and 24 h after administration.…”
Section: Chemicalmentioning
confidence: 99%
“…As described in previous studies on the absorption of EGCG, 13,14) the pharmacokinetic parameters were calculated using a two-compartment model for intravenous administration of EGCG and O-methyl EGCG by the method of residuals. Each pharmacokinetic parameter was calculated as follows:…”
Section: Chemicalmentioning
confidence: 99%
“…However, it should be borne in mind that the anti-Alzheimer potential identified in vitro is not necessarily reproduced in vivo, because factors such as bioavailability and interactivity may influence the behavior of these agents. It has been shown that the polyphenols herein studied are bioavailable and can penetrate the blood-brain barrier (BBB), at least in animal research models (BREUER et al, 2006;LIN et al, 2007). Sakamoto et al (2007) describe the effects of supplementing the diet of adult gerbils with DHA and uridine monophosphate (UMP), which increased the density of spinal dendrites in the hippocampus of these animals and of phosphatides in neuronal membranes.…”
Section: Sgarbieri V C; Pacheco M T Bmentioning
confidence: 99%
“…33 Our laboratory experiment receives possible therapeutic relevance from two sides: Animal experiments indicate the penetration of EGCG across the BBB. 9,10 Coincidentally, moderate irradiances (*kWm -2 ) of red to NIR light, including 670 nm, penetrate several centimeters of tissue, including the cranial bone, delivering therapeutically relevant irradiances. For example, in the case of extreme cardiac dysrhythmia with characteristic symptoms of angina pectoris, 30 min transcostal cardiac stimulation with a battery of seven 670-nm lasers, each 50 mW, pulse frequency 1 Hz, resulted in an instant normalization of the heart rhythm and total disappearance of the angina symptoms (A.P.…”
mentioning
confidence: 99%